2018
DOI: 10.1155/2018/5968431
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Response of a Tunnel Embedded in Compacted Clay through Large‐Scale Shake Table Testing

Abstract: To investigate the seismic response of large-scale tunnel in compacted clay and effect of shock absorbing layer to the tunnel, a series of three dimensional (3D) shaking table model tests were carried out. The similarity ratio of the model is 1 : 8 and the size of the model container is 9.3 m (length) × 3.7 m (width) × 2.5 m (height). The cross-sectional diameter of the model tunnel is 0.9 m, and the thickness of the tunnel lining is 0.06 m. To simulate the clay soil surrounding condition, the container was fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Wu Honggang et al [8] adopted hard PVC as the main material and applied a mixture of gypsum, quartz sand, and water as a 5 mm thick shell to complete the production of the lining model; D. K. Singh et al [9] used different materials to simulate damaged and undamaged tunnels and studied the seismic performance of damaged tunnels in aftershocks. Hao Zhou [10] studied the seismic dynamic response of a large-section tunnel in compacted clay by filling a container with clay soil; Cho Mya Darli [11] carried out a series of shaking-table tests on the integrated corridor tunnel in the mixed stratum of sand and clay, and the results showed that the dynamic response of the tunnel was significantly different in the clay and sandy stratum.…”
Section: Introductionmentioning
confidence: 99%
“…Wu Honggang et al [8] adopted hard PVC as the main material and applied a mixture of gypsum, quartz sand, and water as a 5 mm thick shell to complete the production of the lining model; D. K. Singh et al [9] used different materials to simulate damaged and undamaged tunnels and studied the seismic performance of damaged tunnels in aftershocks. Hao Zhou [10] studied the seismic dynamic response of a large-section tunnel in compacted clay by filling a container with clay soil; Cho Mya Darli [11] carried out a series of shaking-table tests on the integrated corridor tunnel in the mixed stratum of sand and clay, and the results showed that the dynamic response of the tunnel was significantly different in the clay and sandy stratum.…”
Section: Introductionmentioning
confidence: 99%
“…He et al [18] adopted 22 actual recorded ground motions according to the recommendations of the Applied Technology Council (ATC) in the FEMA P695 report in the seismic fragility analysis of multiage buried steel pipes. Since it is difficult to find the ground motions that fully comply with the lithology properties of where the structure is located and with the law of seismic wave propagation, the accuracy of the seismic fragility assessment based on actual recorded ground motions is relatively low [19,20]. e second is synthesizing ground motions.…”
Section: Introductionmentioning
confidence: 99%
“…Taking the Longmen Mountain Fault Zone in the north-western margin of the Sichuan Basin as an example, an earthquake in this fault zone would impact a large number of traffic tunnels and underground structures. e subway stations and other underground structures were critically damaged [2,3] in the Kobe earthquake in Japan, which were considered aseismic structures [4][5][6][7] in highintensity earthquake area. e Lushan earthquake (Ms � 7.0, 2013), the Jiuzhaigou earthquake (Ms � 7.0, 2017), and the Changning earthquake (Ms � 6.0, 2019) show that the tunnels within the Sichuan Basin are threatened by highintensity earthquakes.…”
Section: Introductionmentioning
confidence: 99%